7h+18-h+12=-54

Simple and best practice solution for 7h+18-h+12=-54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7h+18-h+12=-54 equation:


Simplifying
7h + 18 + -1h + 12 = -54

Reorder the terms:
18 + 12 + 7h + -1h = -54

Combine like terms: 18 + 12 = 30
30 + 7h + -1h = -54

Combine like terms: 7h + -1h = 6h
30 + 6h = -54

Solving
30 + 6h = -54

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + 6h = -54 + -30

Combine like terms: 30 + -30 = 0
0 + 6h = -54 + -30
6h = -54 + -30

Combine like terms: -54 + -30 = -84
6h = -84

Divide each side by '6'.
h = -14

Simplifying
h = -14

See similar equations:

| -5-q=0 | | w+.5w+.20= | | X^4-16x^2+6561=0 | | 5m^4+2m^2-7=0 | | -9x+3=5 | | 3x-(x-1)=2(x-3)+9 | | x^2-24xy+144y^2=0 | | 4x-3=-2x | | -11=3x-2 | | 8(2n+6b+8h)= | | (2x-1)+3=57 | | (x+24)-35=19 | | 3x-(x+1)=2(x+1)+1 | | 6-(2n-9)=5-3n | | 4-5y=-11 | | =42y-30 | | 6x+7=4-(8x-4) | | 176=8(1-3x) | | 14x+7=4x+8 | | 42y-30= | | 9x-(x-6)=8(x-2)-8 | | 6(m+2n+9)= | | 2x+4x=6-2x+19 | | (3q)*(4p)=0 | | (2x-5)(5x-10)=90 | | 5x+7=89-7x | | 440=3w-60 | | -.25x+.5=.125x+.333 | | 9x-(x-8)=8(x+3)+4 | | 21(9+w+4n)= | | 2x-5+5x-10=90 | | 2(260+-2y)+4y=520 |

Equations solver categories